Approximate Calculation for Deformation of Multi-Tower Suspension Bridges. Issue 1 (1st February 2016) - Chai, Shengbo; Xiao, Rucheng; Wang, Xiulan
Abstract: This paper presents a method for solving tower deformation and girder deflection in multi-tower suspension bridges. An equivalent model is proposed to simulate a multi-tower suspension bridge in which the towers and main cables are treated as a series of springs. This model can be used for cases of live load acting on one or more spans, and the simple explicit formulas can be used to resolve deformation of the towers and girders as well as for the increment of horizontal cable force in the loaded span. The superposition principle can be used for live loads acting on more than one main span. This paper also presents a finite element model (FEM) of a multi-span suspension bridge with five towers and six spans to verify the analytical formula. Results calculated with the FEM show good agreement with those of the proposed method. This indicates that the proposed method is effective for the preliminary analysis and design of multi-tower suspension bridges.